Differential localization and characterization of functional calcitonin gene‐related peptide receptors in human subcutaneous arteries. (7th January 2014) - Edvinsson, L.; Ahnstedt, H.; Larsen, R.; Sheykhzade, M.
Abstract Aim Calcitonin gene‐related peptide (CGRP) and its receptor are widely distributed within the circulation and the mechanism behind its vasodilation not only differs from one animal species to another but is also dependent on the type and size of vessel. The present study examines the nature of CGRP‐induced vasodilation, characteristics of the CGRP receptor antagonist telcagepant and localization of the key components calcitonin receptor‐like receptor (CLR) and receptor activity modifying protein 1 (RAMP1) of the CGRP receptor in human subcutaneous arteries. Methods CGRP‐induced vasodilation and receptor localization in human subcutaneous arteries were studied by wire myograph in the presence and absence of the CGRP receptor antagonist telcagepant and immunohistochemistry respectively. Results At concentrations of 1, 3, 5, 10 and 30 nm, telcagepant had a competitive antagonist‐like behaviour characterized by a parallel rightwards shift in the log CGRP concentration‐tension/calcium curve with no depression of the maximal relaxation. CGRP‐induced vasodilation was not affected by mechanical removal of the endothelium or addition of L‐NG‐nitroarginine methyl ester and indomethacin, antagonists for synthesis of nitric oxide and prostaglandins, respectively. CLR and RAMP1 were localized in the vascular smooth muscle and endothelial cells. Conclusion The present results indicate that CGRP exerts its vasodilatory effect in human subcutaneous arteries by binding to its receptors located on the smooth muscle cells and is suggested to be endothelium‐independent. In conclusion, these results underline the dynamic distribution of CGRP receptor components in the human circulation reflecting the important role of CGRP in fine tuning of the blood flow in resistance arteries.